(untitled) (Revista Contexto & Educação, 2026)
This paper addresses the inherent difficulties in teaching Spatial Geometry, as well as the paradigmatic shifts in instructional approaches to this topic. The study’s objective is to analyze the relationship between the guidelines present in teacher manuals for Spatial Geometry, found in textbooks from the National Textbook Program (PNLD 2020-2024 quadrennium), and the principles of Didactic Engineering for Teacher Training (DETT). The methodology encompasses the first phase of Didactic Engineering – preliminary analyses – and is based on the examination of three textbook collections developed in alignment with the Brazilian Common Core Standards (BNCC) and the new guidelines for Secondary Education. The aim is, therefore, to relate the approach to Spatial Geometry in the selected guides to DETT’s assumptions, seeking to propose reflections and possible improvements for teaching. The results indicate a close relationship between the didactic guides and DETT, highlighting this engineering’s potential to enhance teacher training and promote effective didactic strategies.